Clinical, functional and radiographic consequences of achieving stable low disease activity and remission with adalimumab plus methotrexate or methotrexate alone in early rheumatoid arthritis: 26-week results from the randomised, controlled OPTIMA study. Issue 1 (5th May 2012) - Kavanaugh, Arthur; Fleischmann, Roy M; Emery, Paul; Kupper, Hartmut; Redden, Laura; Guerette, Benoit; Santra, Sourav; Smolen, Josef S
Abstract : Objective: To assess the efficacy and safety of adalimumab plus methotrexate (ADA+MTX) compared with methotrexate monotherapy in achieving stable low disease activity (LDA; disease activity score (DAS28(CRP)) <3.2 at weeks 22 and 26) and clinical, radiographic and functional outcomes in methotrexate-naive patients with early rheumatoid arthritis (RA). Methods: 1032 patients with active RA were randomly assigned 1:1 to ADA+MTX or placebo plus methotrexate (PBO+MTX) for 26 weeks. Treatment modifications were to be made in a subsequent study period based on the achievement of DAS28(CRP) <3.2 at weeks 22 and 26. Post-hoc analyses compared patients achieving stable remission using DAS28 and 2010 ACR/EULAR criteria with those achieving LDA but not remission. Results: Among patients completing 6 months, 44% (207/466) ADA+MTX versus 24% (112/460) PBO+MTX patients achieved stable LDA at weeks 22 and 26 (p<0.001). Combination therapy was statistically superior to methotrexate in obtaining higher ACR20/50/70 responses, more clinical remissions, greater mean reductions in DAS28(CRP), no radiographic progression, and normal functional status at week 26 (p<0.001 for all). The only factor predicting stable LDA was disease activity at week 12. Patients achieving ACR/EULAR remission, particularly in the PBO+MTX group, had some advantage in radiographic outcomes compared with patients who only achieved LDA (but not remission). The overall frequency of adverse events was comparable between groups. There were more serious infections and deaths in the ADA+MTX group, with a possible age effect. Conclusions: Treatment with ADA+MTX was significantly superior to methotrexate alone with respect to clinical, radiographic and functional outcomes in patients with early active RA. Before initiating treatment with adalimumab, individual patient evaluation of the benefit/risk ratio should be carefully considered.